Alcohol Intoxication Is Associated With Bladder Injury and Bladder Surgical Repair in Patients Sustaining Motor Vehicle Collisions. Issue 5 (2nd November 2022) - Lui, Jason L.; Hakam, Nizar; Shaw, Nathan M.; Cuschieri, Joseph; Abbasi, Behzad; Breyer, Benjamin N.
Abstract : Purpose: Alcohol intoxication is a known risk factor for motor vehicle collisions. We hypothesize ethanol intoxication increases the risk of bladder injury and surgical repair, especially at higher blood alcohol content levels. Materials and Methods: We identified all patients involved in motor vehicle collisions from the National Trauma Data Bank from 2017-2019. Patients were categorized into an intoxication and intoxication negative group. Variables collected included age, sex, blood alcohol content level, driver status, seat belt restraint use, nonalcoholic intoxication, pelvic fracture, and Injury Severity Scale. Primary outcome measures of bladder injury and bladder surgical repair were assessed and interaction with pelvic fracture and restraint use were measured. Results: We identified 594, 484 patients and 97, 831 (16.5%) had a positive alcohol screen. Patients in the intoxication group were more likely to be intoxicated with other substances (32.8% vs 14.6%, P < .001), have a bladder injury (1% vs 0.4%, P < .001) and receive bladder surgical repair (0.7% vs 0.15%, P < .001). Injury Severity Scale and pelvic fracture were statistically significant predictors of bladder injury. In adjusted analysis, higher blood alcohol content was associated with both outcomes. Above the legal limit, alcohol intoxication was more predictive of bladder surgical repair than pelvic fracture. The association of alcohol intoxication with both outcomes did not differ by pelvic fracture, but strengthened with seat belt use at higher intoxication levels. Conclusions: Alcohol intoxication is independently associated with increased risk of bladder injury and subsequent bladder surgical repair following motor vehicle collisions. Trauma providers should have a high index of suspicion for bladder injuries in alcohol intoxicated patients, particularly those using seat belt restraints.